The Influence of Entrepreneurial Principals Competence on School Performance at Al-Musaddadiyah foundation - Nuryanti, B Lena; Mubarok, Abdullah; Lubis, Asep Ridwan (Business Education Program of Universitas Pendidikan Indonesia, 2025)
This study examines the influence of principals' entrepreneurial competence on school performance at Al- Musaddadiyah Foundation in Garut, using both descriptive and verificative approaches. The research findings indicate that entrepreneurial competence, comprising knowledge, ability, and skill, has an overall positive and significant impact on school performance, with a total determination coefficientof77%. Simultaneously,thethreecomponentsof entrepreneurial competence show a positive influence;and in partial analysis knowledge, ability and skill demonstrate significant effects. These findings highlight the importance of developing principals' entrepreneurial competence to enhance school performance and provide significant implications for business education in integrating entrepreneurial values into the educational system. This integration aims to cultivate individuals who are creative, innovative, and capable of identifying opportunities in both educational and business contexts.